2015
DOI: 10.3923/ecologia.2015.43.53
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ichthyofaunal Assemblage of Erelu Reservoir, Oyo, Nigeria

Abstract: Fisheries of Erelu reservoir, South Western Nigeria was assessed using fleet of gillnets of varied mesh sizes with the intent of generating necessary data that could support sustainable use and management of the resources to enhance the socio-economic status of the riparian communities. The reservoir was stratified into upper, middle and lower zones covering an average of 1000 m each and gillnets was deployed to the shores and open water region in each zones monthly for 21 months covering 2 wet and 2 dry seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…This finding implies the high number and dominance of these families in the South West, Nigeria. However, differences in fish composition of this water body and that reported by Falaye et al (2015) could be attributed overexploitation of C. nigrodigitatus from Erelu Reservoir. It could also be due to migration, recruitment, differences in time, gear and climatic condition.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This finding implies the high number and dominance of these families in the South West, Nigeria. However, differences in fish composition of this water body and that reported by Falaye et al (2015) could be attributed overexploitation of C. nigrodigitatus from Erelu Reservoir. It could also be due to migration, recruitment, differences in time, gear and climatic condition.…”
Section: Discussioncontrasting
confidence: 55%
“…Also, Adeosun et al (2010) and Odulate (2016) reported similar findings in their study of both Ikere gorge, Oyo State and Asejire Lake, Ogun State both in the South West of Nigeria. Falaye et al (2015) reported that of the total catch from Erelu Reservoir, Oyo State, 72% were dominated by O. niloticus, Raiamas senegalensis, C. nigrodigitatus, Sarotherodon melanotheron, S. mystus and T. marie. This finding implies the high number and dominance of these families in the South West, Nigeria.…”
Section: Discussionmentioning
confidence: 99%